Forest code and practical applications in small farm - Balestrin, Diego; Balbinot, Rafaelo; Valerius, Jaqueline (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/2236117010748 Nowadays, environmental issues are increasingly present in the everyday life of society, so it is necessary to generate goods and services respecting and preserving the environment, because the economic development of a country is fundamental for the well-being, and improvement in living conditions of the population, and this life quality is only possible with a healthy and balanced environment. In the vast majority of rural properties, not only in the municipalities concerned in this research, but also throughout the state of Rio Grande do Sul and in the country as a whole, there is a violation in the current Forestry Code, is it not applied for lack of knowledge from the population, neglect, or even through lack of supervision of environmental agencies. Different soil uses in rural properties from the Médio Alto Uruguai region, in the state of Rio Grande do Sul, were mapped, and it was found its suitability or not suitability to the forestry code, analyzing the effect of its fulfillment, on land use in small rural properties. The evaluations of this work show the true reality of small-scale agriculture in the region, which are the applications of the code that caused major changes in the properties, and their impacts on the property, thus, a future work based on factors that need to be improved and corrected on each property, for the same being up to date with the current Forestry Code.